Inequalities in antenatal care in Ghana, 1998-2014 - Abdul-Aziz Seidu; Joshua Okyere; Eugene Budu; Henry Ofori Duah; Bright Opoku Ahinkorah (BMC, 2022)
Abstract Background In order to effectively and efficiently reduce maternal mortality and ensure optimal outcomes of pregnancy, equity is required in availability and provision of antenatal care. Thus, analysis of trends of socio-economic, demographic, cultural and geographical inequities is imperative to provide a holistic explanation for differences in availability, quality and utilization of antenatal care. We, therefore, investigated the trends in inequalities  in four or more antenatal care visits in Ghana, from 1998 to 2014. Methods We used the World Health Organization's (WHO) Health Equity Assessment Toolkit (HEAT) software to analyse data from the 1998 to 2014 Ghana Demographic and Health Surveys. We disaggregated four or more antenatal care visits by four equality stratifiers: economic status, level of education, place of residence, and sub-national region. We measured inequality through summary measures: Difference, Population Attributable Risk (PAR), Ratio, and Population Attributable Fraction (PAF). A 95% uncertainty interval (UI) was constructed for point estimates to measure statistical significance. Results The Difference measure of 21.7% (95% UI; 15.2-28.2) and the PAF measure of 12.4% (95% UI 9.6-15.2) indicated significant absolute and relative economic-related disparities in four or more antenatal care visits favouring women in the highest wealth quintile. In the 2014 survey, the Difference measure of 13.1% (95% UI 8.2-19.1) and PAF of 6.5% (95% UI 4.2-8.7) indicate wide disparities in four or more antenatal care visits across education subgroups disfavouring non-educated women. The Difference measure of 9.3% (95% UI 5.8-12.9) and PAF of 5.8% (95% UI 4.7-6.8) suggest considerable relative and absolute urban-rural disparities in four or more antenatal care visits disfavouring rural women. The Difference measure of 20.6% (95% UI 8.8-32.2) and PAF of 7.1% (95% UI 2.9-11.4) in the 2014 survey show significant absolute and relative regional inequality in four or more antenatal care  visits, with significantly higher coverage among regions like Ashanti, compared to the Northern region. Conclusions We found a disproportionately lower uptake of four or more antenatal care visits among women who were poor, uneducated and living in rural areas and the Northern region. There is a need for policymakers to design interventions that will enable disadvantaged subpopulations to benefit from four or more antenatal care visits to meet the Sustainable Development Goal  3.1 that aims to reduce the maternal mortality ratio (MMR) to less than  70/100, 000 live births by 2030. Further studies are essential to understand the underlying factors for the  inequalities in antenatal care visits.